2022
DOI: 10.3390/su14053064
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing a Food Production Site Using Wearable Devices: The Indirect Impact of Immersion and Presence in VR Tours

Abstract: Virtual reality (VR) is among the main technologies revolutionizing numerous sectors, including tourism. In the latter context, virtual tours (VTs) are finding increasing application. Providing an immersive and realistic human–machine interaction, VR tours can bring visitors to virtually experience destination areas. The proposed research presents a theoretical and empirical investigation of the role played by some technical VR features (i.e., presence, immersion, ease-of-use) on VR visitors’ enjoyment, satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…VR and AR can play a promising role in (1) Research and development: VR and AR can be used to simulate different conditions and scenarios to help researchers better understand the CM production process and identify areas for improvement (Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (2) Training and education: VR and AR can be used to train employees on how to handle and process CM. For example, VR simulations can be used to teach employees how to operate equipment and follow safety protocols (De Canio et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (3) Quality control and inspection: AR technology can be used to inspect CM products for defects or inconsistencies, allowing for more efficient and accurate quality control processes (Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (4) Marketing and consumer education: VR and AR can be used to showcase CM products to consumers and educate them about the benefits of CM. This could include virtual tours of CM production facilities or interactive AR experiences that show the environmental benefits of CM (De Canio et al, 2022; Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021).…”
Section: Implementation Of Industry 40 In CM Productionmentioning
confidence: 99%
“…VR and AR can play a promising role in (1) Research and development: VR and AR can be used to simulate different conditions and scenarios to help researchers better understand the CM production process and identify areas for improvement (Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (2) Training and education: VR and AR can be used to train employees on how to handle and process CM. For example, VR simulations can be used to teach employees how to operate equipment and follow safety protocols (De Canio et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (3) Quality control and inspection: AR technology can be used to inspect CM products for defects or inconsistencies, allowing for more efficient and accurate quality control processes (Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021); (4) Marketing and consumer education: VR and AR can be used to showcase CM products to consumers and educate them about the benefits of CM. This could include virtual tours of CM production facilities or interactive AR experiences that show the environmental benefits of CM (De Canio et al, 2022; Chai et al, 2022; Crofton et al, 2019; Jagtap et al, 2021).…”
Section: Implementation Of Industry 40 In CM Productionmentioning
confidence: 99%
“…For example, Flavia´n et al (2019) discussed how the implementation of virtual technology would enhance viewers' emotional reactions and engagement. De Canio et al (2022) found that as the utility, ease-of-use and interactivity of VR/AR increase, the perceived enjoyment and satisfaction of the user also increase, thus giving rise to stronger impulse buying behavior.…”
Section: Cluster 3-vr Experiencesmentioning
confidence: 99%
“…The consequences of a sense of presence have attracted researchers’ attention. Presence leads directly to user enjoyment and affects VR tour satisfaction and visit intention (De Canio et al, 2022). Presence is a key driver of tourists’ attitudes and behaviors in virtual tours (Bogicevic et al, 2019), and can lead to improved users’ attitudes toward the brand and booking intention in the hotel context (Lyu et al, 2021).…”
Section: Hot Topics For Research According To Co-occurring Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The study in [14] has proved how technology converts the traditional learning and museum visit can become an enjoyable platform of learning, increasing the motivation and making it easier to understand building structures and unique architectural details [10]. Moreover, virtual tours increase users' desire to visit the real place [15] and improve the learning outcomes and knowledge retention [16], but, as evidenced in [17], a great result for site or destination managers is that virtual tours do not replace the experience of a real visit.…”
Section: Related Workmentioning
confidence: 99%